Piezoelectric Pre-Stressed Bending Mechanism For Impact-Driven Energy Harvester - Abdal Kadhim, Ali Mohammed; Kok, Swee Leong (Institute Of Physics (IOP) Publishing, 2017)
This paper experimentally demonstrates and evaluates a piezoelectric power generator bending mechanism based on pre-stressed condition whereby the piezoelectric transducer being bended and remained in the stressed condition before applying a force on the piezoelectric bending structure, which increase the stress on the piezoelectric surface and hence increase the generated electrical charges. An impact force is being exerted onto bending the piezoelectric beam and hence generating electrical power across an external resistive load. The proposed bending mechanism prototype has been manufactured by employing 3D printer technology in order to conduct the evaluation. A free fall test has been conducted as the evaluation method with varying force using a series of different masses and different fall heights. A rectangular piezoelectric harvester beam with the size of 32mm in width, 70mm in length, and 0.55mm in thickness is used to demonstrate the experiment. It can be seen from the experiment that the instantaneous peak to peak AC volt output measured at open-circuit is increasing and saturated at about of 70V when an impact force of about 80N is being applied. It is also found that a maximum power of about 53mW is generated at an impact force of 50N when it is connected to an external resistive load of 0.7KΩ. The reported mechanism is a promising candidate in the application of energy harvesting for powering various wireless sensor nodes (WSN) which is the core of Internet of Things (IoT).